Anion Inhibition Profile of the β-Carbonic Anhydrase from the Opportunist Pathogenic Fungus Malassezia restricta Involved in Dandruff and Seborrheic Dermatitis - Sonia Del Prete; Andrea Angeli; Cynthia Ghobril; Julien Hitce; Cécile Clavaud; Xavier Marat; Claudiu T. Supuran; Clemente Capasso (Metabolites, 2019)
Carbonic anhydrases (CAs, EC 4.2.1.1) are ubiquitous metalloenzymes, which catalyze the crucial physiological CO2 hydration/dehydration reaction (CO2 + H2O ⇌ HCO3− + H+) balancing the equilibrium between CO2, H2CO3, HCO3− and CO32−. It has been demonstrated that their selective inhibition alters the equilibrium of the metabolites above affecting the biosynthesis and energy metabolism of the organism. In this context, our interest has been focalized on the fungus Malassezia restricta, which may trigger dandruff and seborrheic dermatitis altering the complex bacterial and fungal equilibrium of the human scalp. We investigated a rather large number of inorganic metal-complexing anions (a well-known class of CA inhibitors) for their interaction with the β-CA (MreCA) encoded by the M. restricta genome. The results were compared with those obtained for the two human α-CA isoforms (hCAI and hCAII) and the β-CA from Malassezia globosa. The most effective MreCA inhibitors were diethyldithiocarbamate, sulfamide, phenyl arsenic acid, stannate, tellurate, tetraborate, selenocyanate, trithiocarbonate, and bicarbonate. The different KI values obtained for the four proteins investigated might be attributed to the architectural features of their catalytic site. The anion inhibition profile is essential for better understanding the inhibition/catalytic mechanisms of these enzymes and for designing novel types of inhibitors, which may have clinical applications for the management of dandruff and seborrheic dermatitis.